BMC Bioinformatics - Zandomeneghi, Sara.; SpringerLink (Online service) (London : BioMed Central : Imprint: BioMed Central.)
BMC Bioinformatics is an open access, peer-reviewed journal that considers articles describing novel computational algorithms and software, models and tools, including statistical methods, machine learning and artificial intelligence, for the modelling and analysis of all kinds of biological data, as well as systems biology. BMC Bioinformatics welcomes manuscripts in the following broad areas of research: Analysis and modelling of complex systems Comparative genomics Data visualization Imaging, and image analysis Knowledge-based analysis Machine learning and artificial intelligence in bioinformatics Network analysis Proteomics Sequence analysis Structural analysis Transcriptome analysis As a BMC Series journal, BMC Bioinformatics does not make editorial decisions based on the perceived interest or potential impact of a study. Manuscripts are considered for publication if they are scientifically valid. For research articles, this includes having a clearly defined and sound research question, appropriate methodology and analysis, and adherence to community-agreed standards relevant to the field.
Keywords: Bioinformatics; Bioinformatics; Algorithms; Bioinformatics; Computational and Systems Biology; Algorithms